Images of the Lithuanian Political Elite in the Eyes of Citizens - Vaičiukynaitė, Justina (Politologija, 2020)
The article aims to reconstruct the concept of the Lithuanian political elite from the citizens’ perspective, focusing on how the concept is perceived, how the political elite is recognized in social life, and what attributes are associated with this particular concept. Applied qualitative in-depth interview data gathering and inductive data analysis approaches demonstrate that the Lithuanian political elite concept consists of two images: legalistic and charismatic. Although these two images are completely divergent, they are intertwined and successfully coexistent in the minds of citizens. The citizens are tending to apply either a legalistic or charismatic image depending on the circumstances: the legalistic image is applied in recognizing and describing the political elite as an externally existing referent; meanwhile, the charismatic image is applied in building up the normative political elite portrait.
Keywords: political elite; elite-mass cleavage; logic of political choice; power; legitimate ruling